Processo de acompanhamento de egressos do curso de atendimento educacional especializado - Silva, Zanandrea Guerch da (2016)
The present study is part of the line of research Gestão das Tecnologias Educacionais em Rede in the Master's Program Tecnologias Educacionais em Rede intended to propose guidelines for the construction of a follow-up of graduates of the course on Special Education Services (Atendimento Educacional Especializado - AEE), offered the distance by this University, gathering information about the destination, employability and professional trajectory. In order to carry out this study, some theorists were used as theoretical background for the guiding principles such as inclusion policies, online teacher development courses, teacher development/training courses for teachers to work with Special Education Services, distance education management, and the process of keeping track of former students. The methodology used was an exploratory and descriptive research, that is, a case study in which the subjects were teachers who are former students of the 10th teacher development/training course for teachers to work with Special Education Services. A semistructured questionnaire with close-ended and open-ended questions was used as the research tool and the data analysis through on the analysis of the content, which brought up three categories that are former student’s profile, professional status, and practice in the course. In conclusion, a process that keeps track of former students helps gather information which will contribute to quality management of online courses as well as obtain feedback about the professionals who are graduatingThus, the proposed objectives have been achieved.